ANALISIS GENRE FILM HOROR KOMEDI INDONESIA DALAM FILM “AGAK LAIN” KARYA MUHADKLY ACHO - Mardiah, Mardiah; Yuliana, Azmi; Wardah, Yulia; Siahaan, Hasnah (Fakultas Agama Islam Universitas Al Washliyah, 2024)
Researchers took the comedy horror film entitled